Factors Affecting Stock Return of Firms Listed in Tehran Stock Exchange: Meta-analysis Approach - Bagher Asgarnezhad Nouri (Journal of Asset Management and Financing, 2018)
The purpose of this study is to investigate the factors influencing firms 'stock return using meta-analysis approach. The study population consists of studies that had examined factors affecting stock returns of listed firms in Tehran Stock Exchange. Accordingly, a total of 89 different research are selected. Based on the literature review, the following factors are considered; liquidity ratios, leverage ratios, activity ratios, profitability ratios, multiple ratios cash flow ratios, risk indicators, earning management indicator, earning forecast, real investment and firm characteristics. The results show that the effect of liquidity ratios, leverage ratios, activity ratios, earning management indicator and firm characteristics on stock return are not significant. But the positive effect of profitability ratios consists of return on equity, profit and profit margin, market-based ratios consist of market return, cash flow ratios consist of cash flow based on operations, risk indicators including market risk premium, indices of earning forecast including the time horizon of profit forecasts and eventually real investment are confirmed.